THE PROBLEM OF MODIFYING AN ALUMINUM-SILICON EUTECTIC ALLOY OF SILUMINS. WAY OF SOLUTIONS - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия, 2018)
It is shown that modern industrial modifiers of silumin eutectic contribute to the saturation of the melt with hydrogen. Its micro bubbles block the branching of eutectic crystals and promote the formation of gas porosity in castings.To improve the efficiency of the process of modifying the eutectic and reduce the gas porosity, a method of hereditary modification is proposed. A special technology has been developed to solve the problem of modification of silumin eutectic.